Quantitative Analyses of Microwave-Treated HiPco Carbon Nanotubes Using Absorption and Raman Spectroscopy - Priya, B. R; Byrne, H. J (Journal of physical chemistry. C, 2009)
As-produced samples of HiPco single-walled carbon nanotubes were subject to microwave radiation treatment, a process which has been reported to selectively destroy metallic nanotubes, leaving samples of predominantly semiconducting nanotubes. Raman measurements of samples exposed for differing durations demonstrate the preferential degradation of metallic nanotubes. UV−vis−NIR absorption spectroscopy demonstrates however that metallic tubes of different diameters degrade at different rates and that prolonged exposure results in the degradation of semiconducting nanotubes. The reaction process was monitored as a function of exposure time through variations in the graphitic band and the radial breathing modes of the Raman spectrum at 633 nm excitation wavelength leading to the determination of the reaction rates and optimum time period for the maximum destruction of metallic tubes. A batch of SWNTs treated under these optimum conditions was produced, and suspensions in 1% aqueous sodium dodecyl benzene sulfonate (SDBS) were prepared. The concentration dependence of the Raman scattering and UV−vis−NIR absorption demonstrated the debundling of the semiconducting bundles to isolated tubes. Extinction coefficients of the bundles and isolated tubes were determined using the Beer−Lambert law. The critical debundling point or dispersion limit was found to be 0.16 ± 0.03 mg/mL compared to the untreated sample which was 0.07 ± 0.03 mg/mL.